2013
DOI: 10.1103/physrevb.87.174101
|View full text |Cite|
|
Sign up to set email alerts
|

First-principles study of possible shallow donors in ZnAl2O4spinel

Abstract: ZnAl 2 O 4 (gahnite) is a ceramic which is considered a possible transparent conducting oxide (TCO) due to its wide band gap and transparency for UV. Defects play an important role in controlling the conductivity of a TCO material along with the dopant, which is the main source of conductivity in an otherwise insulating oxide. A comprehensive first-principles density functional theory study for point defects in ZnAl 2 O 4 spinel is presented using the Heyd, Scuseria, and Ernzerhof hybrid functional (HSE06) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 26 publications
5
21
0
1
Order By: Relevance
“…Considering that ZnAl 2 O 4 is a direct bandgap semiconductor32, the Eg of the ZnAl 2 O 4 samples can be estimated from plots of (αhν)2 versus hν using the Tauc relation33. This is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that ZnAl 2 O 4 is a direct bandgap semiconductor32, the Eg of the ZnAl 2 O 4 samples can be estimated from plots of (αhν)2 versus hν using the Tauc relation33. This is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is a wide band gap material with band gap value of ~3.8 eV in bulk form 11 . It is a n-type semiconducting material, its conductivity prominently attributed to Al Zn antisite defects which is a shallow defect near conduction band edge accompanied by cationic vacancies 12 . Due to complex crystal structure and multiple defect centers such as cationic-anionic vacancies, antisite defects and cationic interstitial, it shows alluring luminescence [6][7][8][9] .…”
mentioning
confidence: 99%
“…Due to complex crystal structure and multiple defect centers such as cationic-anionic vacancies, antisite defects and cationic interstitial, it shows alluring luminescence [6][7][8][9] . Most of the work has been reported on photoluminescence of undoped as well as doped ZnAl 2 O 4 [8][9][10][12][13][14][15][16] . However, in order to understand the defect levels and their nature in a material, it must be studied rigorously, which can be brought about by TL study.…”
mentioning
confidence: 99%
“…Gahnite is characterised by its prominent performance such as high melting temperature (1950°C), low thermal expansion coefficient (5.5 × 10 −6 /°C, 25-1000°C) as well as high thermal stability and good resistance to acids and bases [12]. Gahnite (ZnAl 2 O 4 ) is also a ceramic, which is considered a possible transparent conducting oxide (TCO) due to its wide band gap and transparency in UV [30]. In addition, it has been reported that strontium-hardystonite-gahnite has a significant potential for use in surgical procedures where bone regeneration under load-bearing is required [31].…”
Section: Discussionmentioning
confidence: 99%